Port Competitiveness at Sapangar Bay Container Port from Shipping Lines Perspectives in BIMP EAGA Region - Siti Noraishah Azizan; Shahrin Nasir; Hafidzi Zakaria (Information Management and Business Review, 2023)
Feeder ports in archipelago of the sub-region of BIMP EAGA often face challenges in terms of connectivity due to the dispersed nature of the islands. Realizing the untapped economic potential in the area and the robust geopolitical landscape that has taken place in the last decades, there is an exigency of the countries in BIMP EAGA to improve their port to be the preferred choice by shipping lines. A port's competitiveness holds a paramount significance for shipping lines to call a certain port. Thus, this study aims to examine the perspective of Main Line Operators (MLO) on level of importance of the competitiveness of ports in BIMP EAGA, especially Sapangar Bay Container Port. Ten Main line Operators (MLO) of Intra Asia were selected to respond to the questionnaires using Analytical Hierarchy Process (AHP). The result revealed that the MLO ranked the most important attributes from top to bottom were port efficiency and facilities (EP), port pricing and support services (PP), Hinterland Characteristics (HC), Maritime Accessibility (MA) and lastly Institutional Regulatory (IR). The specific priorities and preferences of shipping lines in this sub-region may be influenced by factors such as trade patterns, port infrastructure, market demands and overall competitiveness of the ports in the region. Findings of this study contribute to the general understanding of port competitiveness in the BIMP EAGA from the perspective of the MLO and may guide the policymakers, port authorities and industry stakeholders in addressing the specific needs and prioritizing their strategic planning to improve the port